2013
DOI: 10.1042/bj20121506
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-dependent lysosomal enlargement in TRPML1-deficient cells involves MTF-1 transcription factor and ZnT4 (Slc30a4) transporter

Abstract: Synopsis Zn is critical for a multitude of cellular processes, including gene expression, secretion and enzymatic activities. Cellular Zn is controlled by Zn-chelating proteins and by Zn transporters. The recent identification of Zn permeability of the lysosomal ion channel TRPML1, and the evidence of abnormal Zn levels in cells deficient in TRPML1, suggested a role for TRPML1 in Zn transport. Here we provide new evidence for such a role and identify additional cellular components responsible for it. In agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 49 publications
4
82
0
Order By: Relevance
“…We used MLIV fibroblasts to verify these findings and to examine a possible rescue effect of MK6-83 on lysosomal zinc accumulation. We found that LysoTracker positive compartments of TRPML1 À / À fibroblasts displayed strong vesicular FluoZin-3 fluorescence when pretreated with ZnCl 2 as described previously 45,46 . The zinc accumulation in TRPML1 À / À fibroblasts was not reversible on treatment with MK6-83.…”
Section: Mk6-83 Effects On Trafficking and Lysosomal Zinc Buildupmentioning
confidence: 84%
See 1 more Smart Citation
“…We used MLIV fibroblasts to verify these findings and to examine a possible rescue effect of MK6-83 on lysosomal zinc accumulation. We found that LysoTracker positive compartments of TRPML1 À / À fibroblasts displayed strong vesicular FluoZin-3 fluorescence when pretreated with ZnCl 2 as described previously 45,46 . The zinc accumulation in TRPML1 À / À fibroblasts was not reversible on treatment with MK6-83.…”
Section: Mk6-83 Effects On Trafficking and Lysosomal Zinc Buildupmentioning
confidence: 84%
“…Different groups have previously reported that zinc accumulates in lysosomes in MLIV fibroblasts or after knockdown of TRPML1 44,45 . Heavy metal accumulation may ultimately lead to the neurodegenerative effects seen in MLIV patients.…”
Section: Mk6-83 Effects On Trafficking and Lysosomal Zinc Buildupmentioning
confidence: 99%
“…The resulting cytoplasmic Zn 2+ spikes were measured using livecell confocal microscopy and FluoZin-3,AM as described previously (Kukic et al, 2013) Fig. 1A shows that the exposure of Baf-treated cells to Zn 2+ caused a significantly higher FluoZin-3,AM response than the exposure of untreated cells to Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…It is tempting to speculate that Zn 2+ export into organelles serves as a first line of defense to provide temporary Zn 2+ storage, giving cells time to upregulate Zn 2+ chelators and transporters. Our recent data on the role of lysosomes in Zn 2+ handling, as well as some recently published results suggest that lysosomes play a role as such Zn 2+ sinks, temporarily storing Zn 2+ (Hwang et al, 2008;Kukic et al, 2013). In this paper, we sought to delineate the role of lysosomes in protection against Zn 2+ -induced toxicity.…”
Section: Cellular Znmentioning
confidence: 99%
See 1 more Smart Citation